2021
DOI: 10.1038/s41598-021-81037-6
|View full text |Cite
|
Sign up to set email alerts
|

Methionine restriction plus overload improves skeletal muscle and metabolic health in old mice on a high fat diet

Abstract: Methionine restriction (MR) has been shown to reduce the age-induced inflammation. We examined the effect of MR (0.17% methionine, 10% kCal fat) and MR + high fat diet (HFD) (0.17% methionine, 45% kCal fat) on body mass, food intake, glucose tolerance, resting energy expenditure, hind limb muscle mass, denervation-induced atrophy and overload-induced hypertrophy in young and old mice. In old mice, MR and MR + HFD induced a decrease in body mass. Muscle mass per body mass was lower in old compared to young mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…2 h). A similar decrease in mass has been reported in other MR studies 4 , 7 , 47 . Further examination of muscle function and structure will be necessary to delineate this potential novel relationship between methionine metabolism and muscle.…”
Section: Discussionsupporting
confidence: 90%
“…2 h). A similar decrease in mass has been reported in other MR studies 4 , 7 , 47 . Further examination of muscle function and structure will be necessary to delineate this potential novel relationship between methionine metabolism and muscle.…”
Section: Discussionsupporting
confidence: 90%
“…2h). A similar decrease in mass has been reported in other MR studies [4,7,47] . Further examination of muscle function and structure will be necessary to delineate this potential novel relationship between methionine metabolism and muscle.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that dietary methionine restriction (MR) in rodents can extend lifespan up to 42% compared to rodents fed diets replete with methionine [1][2][3] . Moreover, MR has strong effects on metabolic function and has been shown to improve glucose homeostasis [4][5][6][7][8][9] , decrease oxidative stress [2,[10][11][12][13][14][15] , and promote adipose tissue browning [16][17][18][19][20][21][22] . These findings are consistent with the idea that dietary intervention by restricting methionine improves health in addition to extending longevity.…”
Section: Introductionmentioning
confidence: 99%
“…However, as any other rodent model, it has its limitations in recapitulating all the hallmarks of the complex disease in humans [ 47 ]. Our study was also performed only in female mice, and given that sex differences in insulin sensitivity have been reported in rat and mouse models, it would be important in future experiments to also explore the same study design in male mice [ 48 - 50 ].…”
Section: Discussionmentioning
confidence: 99%